The Effectiveness of the Mother of Toddlers Class in Improving Postpartum Reproductive Health Care Practices - Ula, Zumrotul (Oshada, 2025)
This study aims to examine the effectiveness of the Mother of Toddlers Class program in improving postpartum mothers’ practices related to reproductive health care. Postpartum is a vulnerable period often marked by insufficient knowledge and lack of supportive services, especially in rural and semi-urban areas. Through a quasi-experimental design, the study involved postpartum mothers from Surabaya, Sidoarjo, and Pasuruan, divided into intervention and control groups. The intervention group participated in a structured educational program covering topics such as perineal hygiene, early detection of postpartum complications, emotional well-being, and family planning. Data were collected through pre- and post-tests, observations, and interviews. The results demonstrated a statistically significant improvement in knowledge, attitudes, and health practices among mothers who attended the program. Contextual factors such as educational background and family support were found to influence the intervention's success. The study concludes that Mother of Toddlers Class is an effective and scalable model for enhancing postpartum care and should be integrated into national maternal health strategies.